PERAN SENSASI DAN PERSEPSI SEBAGAI MEKANISME PENYARING DALAM FENOMENA INFORMATION OVERLOAD - Fatimah, Siti; Adirais, Dzulfikar; Halwati, Umi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The phenomenon of information overload has become a major challenge in the digital era, as the rapid flow of data exceeds human cognitive capacity to absorb, comprehend, and respond effectively. This study employas descriptive qualitative approach through a literature review to explain the role of sensation and perception as filtering mechanisms within intrapersonal communication. The findings indicate that sensation acts as the initial gateaway that limits incoming sensory stimuli, while perception functions as a selective filter that assigns meaning and relevance to information. When these mechanisms are unable to manage the volume and intensity of stimuli, individuals are more likely to experience stress, confusion, cognitive fatigue, and decreased productivity. Beyond emphasizing the importance of internal filtering processes, this study highlights the need for future research, including empirical testing of the dual-filter model of sensation and perception, the development of intervntions such as notification management and information literacy training, and platform specific investigations in digital media environments. Future studies are also encouraged to incorporate neuroscientific approaches and cross-cultural analysis to deepen understanding of cognitive responses to information overload. Overall, the findings underscore the urgency of implementing stimulus management strategies and strengthening cognitive skills to maintain effective learning, work performance, and decision-making in increasingly information dense digital ecosystem.